Evaluation of Regional Surface Energy Budget Over Ocean Derived From Satellites - Kato, Seiji; Rose, Fred G.; Chang, Fu-Lung; Painemal, David; Smith, William L. (Frontiers in Marine Science, 2021)
The energy balance equation of an atmospheric column indicates that two approaches are possible to compute regional net surface energy flux. The first approach is to use the sum of surface energy flux components Fnet,c and the second approach is to use net top-of-atmosphere (TOA) irradiance and horizontal energy transport by the atmosphere Fnet,t. When regional net energy flux is averaged over the global ocean, Fnet,c and Fnet,t are, respectively, 16 and 2 Wm–2, both larger than the ocean heating rate derived from ocean temperature measurements. The difference is larger than the estimated uncertainty of Fnet,t of 11 Wm–2. Larger regional differences between Fnet,c and Fnet,t exist over tropical ocean. The seasonal variability of energy flux components averaged between 45°N and 45°S ocean reveals that the surface provides net energy to the atmosphere from May to July. These two examples demonstrates that the energy balance can be used to assess the quality of energy flux data products.